The effect of owning private long-term care insurance policies on out-of-pocket costs. - Rice, T (1991)
This article examines the effect of owning long-term care insurance policies on the amount of out-of-pocket costs incurred by the elderly during their nursing home stays, and the importance of different policy features and restrictions. Data were drawn from the 1985 National Nursing Home Survey, and from copies of long-term care insurance policies collected from 11 leading companies during the spring and summer of 1988. The study results show a great deal of uncertainty concerning amounts the policies are likely to pay toward nursing home stays. This implies that the policies collected did not adequately fulfill one of the primary purposes of insurance: a reduction in risk and uncertainty. To examine whether rapid policy changes in recent years have made a difference, we assessed each of seven policy features and found that the two most important restrictions in long-term care insurance policies are prior hospitalization and level-of-care requirements. Recently, the National Association of Insurance Commissioners (NAIC) recommended that states prohibit the sale of policies containing these restrictions. Our findings confirm the wisdom of this recommendation. We did find, however, that two other policy restrictions--policy maximums and lack of inflation adjustment--are problematic. We recommend that the NAIC expand its model regulations to require that policy maximums be a minimum of four years, and that some form of inflation protection be incorporated into policy benefit structures.